Fungal mediated kinetic resolution of racemic acetates to (R)-alcohols using fusarium proliferatum - Jadhav, Dipesh D.; Patil, Harshal S.; Chaya, Patil S.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2016)
Fungal mediated kinetic resolution of seven acyclic/aromatic acetates was achieved using Fusarium proliferatum to furnish (R)-alcohols in high enantiomeric excess (>95%). The kinetic resolution was established as one-pot two-step de-esterification/oxidation biocatalytic process. Further, the preparative scale synthesis of (R)-(+)-1-phenylethanol was accomplished through de-esterification/oxidation of (+/-)-1-phenylethyl acetate using the whole cell of F. proliferatum NCIM 1105. (C) 2016 Elsevier Ltd. All rights reserved.

Limonoid biosynthesis 3: functional characterization of crucial genes involved in neem limonoid biosynthesis - Pandreka, Avinash; Chaya, Patil S.; Kumar, Ashish; Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Bhagyashree, Date D.; Shilpashree, H. B.; Jennifer, Cheruvathur; Ponnusamy, Sudha; Nagegowda, Dinesh; Thulasiram, V. Hirekodathakallu (Phytochemistry, 2021)
Neem (Azadirachta indica L.) is well known for its medicinal, agricultural, and pesticidal applications since ages. The secondary metabolites, limonoids, confer these biological properties, wherein over 150 different limonoids have been reported from neem. To understand limonoid biosynthesis, we analyzed tissue-specific (kernel, pericarp, leaves, and flower) transcriptome that resulted in the identification of one farnesyl diphosphate synthase (AiFDS), one squalene synthase (AiSQS), three squalene epoxidases (AiSQE1, AiSQE2, and AiSQE3), two triterpene synthases (AiTTS1 and AiTTS2), cycloartenol synthase (AiCAS), two cytochrome P450 reductases, and ten cytochrome P450 systems. Comparative tissue-expression analysis indicated that AiFDS, AiSQS, AiSQE3, and AiTTS1 are expressed higher in the kernel than in the other tissues. Heterologously expressed recombinant AiTTS1 produced tirucalla-7,24-dien-3 beta-ol as the sole product. Expression profile data, phylogeny with triterpene synthases from Meliaceae and Rutaceae families, real-time PCR of different tissues, and transient transformation revealed the involvement of tirucalla-7,24-dien-3 beta-ol synthase (AiTTS1) in limonoid biosynthesis. Further, mutagenesis studies of AiTTS1 indicated that Y125 and F260 are probably involved in stabilization of dammarenyl cation. A 2.6-fold increase in production of tirucalla-7,24-dien-3 beta-ol was observed when AiSQE1 was coexpressed with mutant AiTTS1 in a yeast system. Furthermore, we functionally characterized the highly expressed cytochrome P450 reductases and cycloartenol synthase. This study helps in further analysis and identification of genes involved in limonoid biosynthesis in Meliaceae/Rutaceae and their production in a metabolically tractable heterologous system.
Keywords: 24-dien-3 beta-ol; Azadirachta indica A. Juss.; Cytochrome P450 system; Limonoids; Meliaceae; Tirucalla-7; Transcriptome

Limonoid biosynthesis 3: functional characterization of crucial genes involved in neem limonoid biosynthesis (vol 184, 112669, 2021) - Pandreka, Avinash; Chaya, Patil S.; Kumar, Ashish; Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Bhagyashree, Date D.; Shilpashree, H. B.; Jennifer, Cheruvathur; Ponnusamy, Sudha; Nagegowda, Dinesh; Thulasiram, Hirekodathakallu V. (Phytochemistry, 2021)